2018
DOI: 10.1038/s41598-018-30846-3
|View full text |Cite
|
Sign up to set email alerts
|

Carbon fiber doped thermosetting elastomer for flexible sensors: physical properties and microfabrication

Abstract: We have developed conductive microstructures using micropatternable and conductive hybrid nanocomposite polymer. In this method carbon fibers (CFs) were blended into polydimethylsiloxane (PDMS). Electrical conductivities of different compositions were investigated with various fiber lengths (50–250 μm), and weight percentages (wt%) (10–60 wt%). Sample composites of 2 cm × 1 cm × 500 μm were fabricated for 4-point probe conductivity measurements. The measured percolation thresholds varied with length of the fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 45 publications
0
40
0
Order By: Relevance
“…The resulting three-dimensional porous nanocomposites, with the CNFs embedded in the PDMS pore walls, exhibit a greatly increased failure strain (up to ∼94%) compared to that of the solid, neat PDMS (∼48%) [23]. More related research on flexible PDMS can be found in References [24,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting three-dimensional porous nanocomposites, with the CNFs embedded in the PDMS pore walls, exhibit a greatly increased failure strain (up to ∼94%) compared to that of the solid, neat PDMS (∼48%) [23]. More related research on flexible PDMS can be found in References [24,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon‐doped inorganic or polymer composite materials have attracted much attention. Different forms of carbon (ie, graphite, diamond, fullerenes, and other all‐carbon polymeric allotropies) can provide composite materials plenty of new functionalities in electronics, optics, and mechanics 1‐3 . Embedding carbon nanostructures into transparent glass is of particular interest for optical studies 3‐5 .…”
Section: Introductionmentioning
confidence: 99%
“…Different forms of carbon (ie, graphite, diamond, fullerenes, and other all-carbon polymeric allotropies) can provide composite materials plenty of new functionalities in electronics, optics, and mechanics. [1][2][3] Embedding carbon nanostructures into transparent glass is of particular interest for optical studies. [3][4][5] The absorptive and emissive properties of carbon nanostructures can be used in devices such as attenuators, saturable absorbers, light-emitting diodes, etc.…”
Section: Introductionmentioning
confidence: 99%
“…With the high demand for ultra-sensitive biodetectors, beam-based micro and nanosystems have emerged and developed recently 11–15 . Their fabrication has also attracted much attention due to its difficulties in the ultra-small scale to reach acceptable accuracy in the instrumentation engineering 2,16 . Recently, it has been reported that fabricating nanobridges from the silicon crystal walls of 30 nm thickness is possible by the application of focused ion beam (FIB) and scanning electron microscopy (SEM) based techniques 17 .…”
Section: Introductionmentioning
confidence: 99%